Mengarahkan Transisi Hijau: Interaksi Tata Kelola Pemerintahan, Efektivitas Keuangan Hijau, dan Transformasi Struktural di Negara Berkembang - Fauzan Sinatra; R Fawwaz Zaidan Pradipa; I Putu Wedana; Muhammad Fadhil Kasmuddin; Arina Romaina; Ardieansyah Ardieansyah; Luthfi Azhari (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
This article aims to critically analyze the interaction between green finance (GF) and green government (GG) in the context of development economics. The main focus is to evaluate how the quality of institutional governance moderates the effectiveness of green finance flows in achieving a sustainable transition. Based on this analysis, this research proposes a new conceptual model. This study uses a Systematic Literature Review (SLR) methodology on Scopus and Sinta-indexed scientific articles, as well as reputable institutional reports (OECD, World Bank, IFC) within the 2020-2025 timeframe. This approach is combined with theoretical model development to synthesize findings. The review identifies a "green finance effectiveness paradox." Although global GF capital flows have rapidly increased (reaching $8.2 trillion in 2024), their effectiveness in emerging markets (EMDEs) is questionable. Evidence shows significant greenwashing risks, where the issuance of instruments like green bonds is not always followed by emission reductions (AMRO, 2025). The review finds the root cause to be institutional; the biggest barrier for private investors is the absence of a comprehensive long-term transition strategy from the government (IFC, 2023). Empirical evidence (Bakry et al., 2023; Zhang et al., 2024) confirms that governance quality (e.g., government integrity, regulatory strength) is a significant determinant of environmental outcomes, indicating its role as a moderating variable. The Indonesian case study highlights a critical implementation gap: policy 'Commitment' (e.g., Green Taxonomy, POJK) is high, but implementation 'Capability' (especially for reaching MSMEs) remains very low (Paramita, 2025). The main contribution of this article is the development of the GG-GF-GST conceptual model. This model frames Green Governance (GG) operationalized through three pillars: Commitment, Capability, and Consensusas a fundamental moderating mechanism that filters (reduces greenwashing) and strengthens (increases effectiveness) Green Finance (GF) flows to achieve the ultimate goal of development economics, namely Green Structural Transformation (GST).